1989
DOI: 10.1111/j.1432-1033.1989.tb15098.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of subunit 4, a nuclear‐encoded protein of the F0 sector of yeast mitochondrial ATP synthase, in the assembly of the whole complex

Abstract: The yeast nuclear gene ATP4, encoding the ATP synthase subunit 4, was disrupted by insertion into the middle of it the selective marker URA3. Transformation of the Saccharomyces cerevisiae strain D273-10R/A/U produced a mutant unable to grow on glycerol medium. The ATP4 gene is unique since subunit 4 was not present in mutant mitochondria; the hypothetical truncated subunit 4 was never detected. ATPase was rendered oligomycininsensitive and the F, sector of this mutant appeared loosely bound to the membrane. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
2

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 46 publications
10
69
0
2
Order By: Relevance
“…ATPase activities of isolated mitochondria. Mitochondria were isolated from cells grown at 28°C with 2% lactate or glycerol as carbon source for the wild-type and complemented SVY15-1 cells and 2% galactose as carbon source for the null mutant SVY14 and the rhocells (the rho-mitochondria are presented as a control; Paul et al, 1989). Measurements were performed in triplicate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ATPase activities of isolated mitochondria. Mitochondria were isolated from cells grown at 28°C with 2% lactate or glycerol as carbon source for the wild-type and complemented SVY15-1 cells and 2% galactose as carbon source for the null mutant SVY14 and the rhocells (the rho-mitochondria are presented as a control; Paul et al, 1989). Measurements were performed in triplicate.…”
Section: Resultsmentioning
confidence: 99%
“…This low respiration rate was mainly the consequence of a high rho-cell content. However, it was previously observed that the absence of a functional F, had an indirect effect on the assembly and activity of the cytochrome oxidase (Choo et al, 1985 ;Paul et al, 1989). Similarly, cytochrome oxidase activities of 0.05 pmol 0, .…”
Section: Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…The slow growth of N417 on rich glycerol/ethanol medium suggests that the genetic lesion does not abolish expression of F 0 totally, which would explain why this strain is able to synthesize subunit 6. Like other ATPase mutants that display a pleiotropic deficiency of cytochrome oxidase (Marzuki et al 1989;Paul et al 1989), most of the atp22 mutants showed a substantial decrease in translation of subunit 1 of this respiratory complex.…”
Section: Resultsmentioning
confidence: 99%
“…Western analysis of ATPase subunits indicated that atp22 point mutants are grossly deficient in subunit 6 (Helfenbein et al 2003). A subunit 6 deficit is not necessarily related to translation of the protein or absence of the mRNA (Ellis et al 2004) but can also be caused by its turnover in mutants defective in F 0 assembly (Paul et al 1989(Paul et al , 2000Arselin et al 1996). In our earlier studies of the atp22 mutant, N417, some incorporation of 35 S-methionine into subunit 6 was observed when cells were labeled in vivo in the presence of cycloheximide to arrest cytoplasmic protein synthesis (Helfenbein et al 2003).…”
Section: Resultsmentioning
confidence: 99%